Odpowiedź :
a)(×-3)(×+3)+5×=×(×-2)
x²-9+5x=x²-2x
x²+5x-x²+2x=9
7x=9/7
x= dziewięć siódmych (ułamek)
b) (y-1)²>y(×+4)-3y
x-oznacza razy
y²+2 x y x 1> xy+4y-3y
y²+2y > xy +4y-3y
y²+2y+3y-4y >xy
y²+y>xy
x²-9+5x=x²-2x
x²+5x-x²+2x=9
7x=9/7
x= dziewięć siódmych (ułamek)
b) (y-1)²>y(×+4)-3y
x-oznacza razy
y²+2 x y x 1> xy+4y-3y
y²+2y > xy +4y-3y
y²+2y+3y-4y >xy
y²+y>xy
2x+y=5
3x-2y=3
y=-2x+5
3x-2*(-2x+5)=3
3x+4x-10=3
7x=13
x=13/7
y=-2*13/7+5
y=-26/7+5
y=1 i dwie siódme
3x-2y=3
y=-2x+5
3x-2*(-2x+5)=3
3x+4x-10=3
7x=13
x=13/7
y=-2*13/7+5
y=-26/7+5
y=1 i dwie siódme